Strengthening leaf physiological functioning and grain yield formation in heat-stressed wheat through potassium application - Sarwar, Muhammad; Saleem, Muhammad Farrukh; Maqsood, Hamza; Ullah, Najeeb; Khan, Aziz; Waqas, Muhammad; Sattar, Nimra; Tasneem, Muhammad; Xu, Xu; Zhangli, Hu; Shuang, Yang (Frontiers in Plant Science, 2022)
Wheat crops are highly sensitive to high temperatures during their reproductive and grain-filling phases. We hypothesized that potassium could increase thermotolerance in wheat during grain filling by protecting cellular organelles, particularly chlorophyll, from heat injury. Two wheat genotypes of varying heat sensitivity were submitted to 4 and 8 days of heat stress one week after anthesis under polythene sheets. One day before the onset of heat stress, 2% potassium (K) as K2SO4 was sprayed on all the plants. Heat-stress recovery mechanism was explored by studying changes in leaf physiology of plants at 7-d after K2SO4 treatment. Increasing duration of heat stress significantly impaired leaf physiology and grain yield of both studied wheat genotypes. Compared with control (under optimum temperature), 4 and 8 d heat-stressed plants produced 11% and 19% lesser grain yield per spike (averaged across genotypes and in the second years of study), respectively. Likewise, 4-d and 8-d heat-stressed plants had 15% and 37% (averaged across genotypes and in the second years of study) lower flag leaf photosynthesis, respectively, compared with control plants. Across the genotypes, 8-d heat caused significantly more grain yield loss in Anaj-2017 during the second year than in Ujala-2016. Foliar K significantly restored leaf chlorophyll, Pn, Fv/Fm by reducing cellular membrane damage in the heat-stressed plants. This physiological recovery protected grain development. For example, K-treated plants produced 19% higher 1000 grain weight in 8 days of heat stress (across genotypes and in the second years of study) compared with water-treated plants under the hot environment of the respective thermal regime. Our study suggests that wheat performance under terminal heat stress can be improved through the exogenous application of K.